Tropical cyclone activity and western North Atlantic stratification over the last millennium: a comparative review with viable connections - Woodruff, Jonathan D.; Sriver, Ryan L.; Lund, David C. (Journal of Quaternary Science, 2012)
Tropical cyclones (TC) are recognized to modify the thermal structure of the upper ocean through the process of vertical mixing. Assessing the role this mixing plays in the overall stratification of the upper ocean is difficult, due to the relatively short and incomplete instrumental record. Proxy records for both TC landfalls and oceanographic stratification are preserved within the geological record and provide insight for how past changes in TC‐induced mixing have potentially affected water column structure prior to the instrumental record. Here we provide the first comparison between previously published paleo‐reconstructions of vertical ocean density and tropical cyclone activity from the western North Atlantic. A prominent lull in TC activity has been observed prior to approximately 1700 CE that extends back several centuries. This interval of low TC activity is shown to be concurrent with the timing of increased ocean stratification near Great Bahama Bank, potentially due in part to reduced TC‐induced mixing. To test whether this relationship is feasible, we present numerical results from a coarse‐resolution ocean general circulation model experiment isolating the effect of TC surface wind forcing on the upper ocean. An anomaly of roughly 0.12 kg m −3 in vertical stratification occurs above and below the mixed layer for model runs with and without TC mixing. This anomaly is roughly 25% of the entire paleo‐density signal observed just prior to 1700 CE. These results suggest that TC mixing alone cannot completely explain the density anomaly observed prior to 1700 CE, but support TC variability as an important contributor to enhancing oceanic stratification during this interval. Copyright © 2011 John Wiley & Sons, Ltd. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/91201/1/1551_ftp.pdf